Meta‐analysis of the impact of neoadjuvant therapy on patterns of recurrence in pancreatic ductal adenocarcinoma. Issue 2 (30th March 2018) - Schorn, S.; Demir, I. E.; Samm, N.; Scheufele, F.; Calavrezos, L.; Sargut, M.; Schirren, R. M.; Friess, H.; Ceyhan, G. O.
Abstract : Background: Neoadjuvant therapy may increase the rate of radical tumour resection in patients with pancreatic cancer. Its impact on tumour recurrence has not been investigated fully. This study aimed to assess the impact of neoadjuvant therapy on patterns of recurrence. Methods: A systematic review was performed of articles identified through the PubMed, Scopus, Embase, Ovid and Google Scholar databases that analysed the relationship between neoadjuvant therapy and recurrence published to January 2016. The main endpoint was overall tumour recurrence. Other endpoints included local recurrence, any kind of distant, hepatic, pulmonary or peritoneal metastasis. Results: A total of 4257 citations were reviewed. Twelve observational studies comprising 1365 patients were analysed. Neoadjuvant therapy significantly reduced the risk of overall (risk ratio (RR) 0·82, 95 per cent c.i. 0·74 to 0·90; P < 0·001) and local (RR 0·42, 0·32 to 0·55; P < 0·001) recurrence. Neoadjuvant therapy did not reduce the risk of any kind of distant (RR 1·02, 0·91 to 1·14; P = 0·78), hepatic (RR 0·86, 0·68 to 1·10; P = 0·23), pulmonary (RR 0·99, 0·37 to 2·66; P = 0·98) or peritoneal (RR 0·88, 0·57 to 1·38; P = 0·58) metastasis. Conclusion: Neoadjuvant therapy reduced the risk of local recurrence but not that of distant metastasis. Abstract : Although neoadjuvant therapy in pancreatic ductal adenocarcinoma is a focus of research, its impact on tumour recurrence has not been assessed systematically. For this purpose, a systematic review with meta‐analysis was undertaken to compare the effect of neoadjuvant therapy in patients with pancreatic ductal adenocarcinoma who received neoadjuvant therapy before surgery with those who underwent direct tumour resection. Neoadjuvant therapy reduced the risk of overall tumour recurrence by decreasing the incidence of local recurrence but did not affect the risk of distant metastasis. Neoadjuvant therapy reduced the risk of local recurrence